WorldFish in Cambodia - Sithirith, Mak (WorldFish, 2024)
WorldFish has worked in Cambodia since 2006, collaborating with the government and development partners to increase productivity and investment in the agriculture and fisheries sectors. Our research focuses on improving the productivity and resilience of wild fisheries in human-modified environments such as rice fields and reservoirs. It provides assistance to the aquaculture sector, expands the role of fish in the nutrition security of women and children, and increases benefit-sharing in land and water management.